2007
DOI: 10.1136/ard.2007.083584
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab efficacy and safety against refractory systemic necrotising vasculitides: long-term follow-up of 15 patients

Abstract: These observations highlight infliximab as a potentially useful and safe salvage treatment for patients with refractory SNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 13 publications
(12 reference statements)
1
28
0
2
Order By: Relevance
“…No study to date has adequately assessed the capacity of TNF blockade to substitute for standard therapies in AAV. A steroid-sparing effect of infliximab has been reported in patients with persistently active AAV [10,23] and in this study the older patients treated with infliximab and a reduced dose of prednisolone achieved clinical remission at the same rate as those younger patients treated with infliximab and a standard dose of prednisolone. Conceivably, infliximab might allow reduction of cumulative corticosteroid and/or cyclophosphamide doses in patients with newly presenting or relapsing AAV.…”
Section: Discussionsupporting
confidence: 55%
“…No study to date has adequately assessed the capacity of TNF blockade to substitute for standard therapies in AAV. A steroid-sparing effect of infliximab has been reported in patients with persistently active AAV [10,23] and in this study the older patients treated with infliximab and a reduced dose of prednisolone achieved clinical remission at the same rate as those younger patients treated with infliximab and a standard dose of prednisolone. Conceivably, infliximab might allow reduction of cumulative corticosteroid and/or cyclophosphamide doses in patients with newly presenting or relapsing AAV.…”
Section: Discussionsupporting
confidence: 55%
“…Based on the beneficial effects of TNF blockade in other chronic inflammatory disorders and the fact that several lines of evidence implicate TNF in the pathogenesis of AAV in humans and animal models of the disease, several small pilot studies evaluated the therapeutic potential of infliximab revealing promising results. However, data derived from subsequent studies were conflicting and could not corroborate any additional benefit from the use of infliximab in patients with AAV (Booth et al 2004;Josselin et al 2008;Morgan et al 2010). It should be noted that there is no RCT for infliximab in AAV.…”
Section: Other Treatmentsmentioning
confidence: 93%
“…Deoxyspergualin (0.5 mg/Kg/day subcutaneously in 6 cycles of 21 days with 7-day intervals), an antiproliferative agent licensed in Japan for acute renal transplant rejection, showed promise in phase II study (Flossmann et al 2009). Infliximab was beneficial in refractory disease in observational studies (Josselin et al 2008) but when added to standard induction treatment did not make any difference ).…”
Section: Refractory Diseasementioning
confidence: 99%
“…In an open study, Bartolucci et al demonstrated that infliximab used in 10 patients (7 with Wegener's granulomatosis) with severe vasculitides refractory to corticosteroids and immunosuppressive agents could also have led to complete or partial remission in all patients [79]. Moreover, infliximab may have a suspensive and transient beneficial effect because of relapses evidenced after discontinuation [80]. Etanercept has also been evaluated in association with conventional therapy to reduce the relapse rate versus placebo in the WGET trial.…”
Section: Systemic Necrotizing Vasculitidesmentioning
confidence: 99%